2020
DOI: 10.1111/oik.07022
|View full text |Cite
|
Sign up to set email alerts
|

On the scaling of activity in tropical forest mammals

Abstract: Activity range – the amount of time spent active per day – is a fundamental aspect contributing to the optimization process by which animals achieve energetic balance. Based on their size and the nature of their diet, theoretical expectations are that larger carnivores need more time active to fulfil their energetic needs than do smaller ones and also more time active than similar‐sized non‐carnivores. Despite the relationship between daily activity, individual range and energy acquisition, large‐scale relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 70 publications
(122 reference statements)
4
23
4
Order By: Relevance
“…Based on this systematic year-long camera-trap study, we found little support for diel activity levels to scale significantly and positively with body mass, or to differ between ruminants and nonruminants, or between herbivores and faunivores. For herbivores, the absence of a body mass scaling resembles the recent finding of Cid et al (2020).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Based on this systematic year-long camera-trap study, we found little support for diel activity levels to scale significantly and positively with body mass, or to differ between ruminants and nonruminants, or between herbivores and faunivores. For herbivores, the absence of a body mass scaling resembles the recent finding of Cid et al (2020).…”
Section: Discussionsupporting
confidence: 72%
“…In these species, terrestrial camera-trap placement may not represent their entire habitat niche and may thus result in biased activity patterns. In addition, our activity analyses are based on the sampled population of a species and did not differentiate between individual-level or sex-specific diel activity patterns, which F I G U R E 3 Relationship of activity levels and body mass from this study as compared to data obtained from 249 populations of terrestrial mammals in the tropics (Cid et al, 2020), distinguished as carnivores, herbivores, insectivores, and omnivores. Note the general overlap of data, that a scaling in herbivores may depend critically on including species smaller than available in the present study, and that the scaling in carnivores may depend critically on whether invertebrate and vertebrate prey are considered different trophic niches or not.…”
Section: Methodological Aspects Of Camera Trapping and Activity Recordingmentioning
confidence: 93%
See 1 more Smart Citation
“…This is consistent with other findings concerning foraging space use: large‐bodied birds, which tend to feed on high‐quality resources and forage over large spatial scales (Schoener 1968), travel farther in homogeneous environments than heterogeneous environments (Tucker et al 2019). Among mammals, trophic level is correlated with home range size (Jetz et al 2004), which is positively correlated with activity levels (Cid et al 2020), suggesting a positive relationship between space use and activity levels over large scales.…”
Section: Discussionmentioning
confidence: 99%
“…These interact when animals forage, as they need to traverse the landscape according to their movement capacities to locate resources distributed non‐randomly in the environment (Suryan et al 2008). To maximize energetic gains from foraging, the timing of an animal's foraging movements is expected to correspond to either the temporal availability of its resources (Rydell et al 1996, Lang et al 2018) or the quantity and quality of resources required (Jetz et al 2004, Ramesh et al 2015, Cid et al 2020). Alternatively, animals can reduce their energy expenditure by timing their foraging activity when their movements are most energetically efficient (Chapman et al 2011, Shepard et al 2013) via behavioral thermoregulation (Matern et al 2000) and passive movement (Krupczynski and Schuster 2008).…”
Section: Introductionmentioning
confidence: 99%